2020
DOI: 10.3390/rs12010193
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty Analysis of Remotely-Acquired Thermal Infrared Data to Extract the Thermal Properties of Active Lava Surfaces

Abstract: Using thermal infrared (TIR) data from multiple instruments and platforms for analysis of an entire active volcanic system is becoming more common with the increasing availability of new data. However, the accuracy and uncertainty associated with these combined datasets are poorly constrained over the full range of eruption temperatures and possible volcanic products. Here, four TIR datasets acquired over active lava surfaces are compared to quantify the uncertainty, accuracy, and variability in derived surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Remote sensing methods based on measuring the infrared (IR) radiance from active lava bodies are widely applied, using spaceborne, airborne or ground-based platforms [2]. However, they are subject to assumptions and caveats that can propagate large uncertainties (±100 K) related to the surrounding environment [3], [4], large temperature gradients of cooling lavas as well as constant changes in their composition and texture during emplacement. Despite that reducing the uncertainties of environmental and thermal gradients when measuring emissivity is ultimately challenging, this study is aimed at minimizing the uncertainty of one of the critical, yet poorly known, parameters namely spectral emissivity (ελ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Remote sensing methods based on measuring the infrared (IR) radiance from active lava bodies are widely applied, using spaceborne, airborne or ground-based platforms [2]. However, they are subject to assumptions and caveats that can propagate large uncertainties (±100 K) related to the surrounding environment [3], [4], large temperature gradients of cooling lavas as well as constant changes in their composition and texture during emplacement. Despite that reducing the uncertainties of environmental and thermal gradients when measuring emissivity is ultimately challenging, this study is aimed at minimizing the uncertainty of one of the critical, yet poorly known, parameters namely spectral emissivity (ελ).…”
Section: Introductionmentioning
confidence: 99%
“…This parameter is crucial to invert remotely-sensed spectral radiance observations of lava at high T, including in the molten state. Only a few laboratory studies have been carried out on this topic, highlighting the technical difficulties for obtaining accurate emissivity data, especially at high temperature [4]- [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…where is the Stefan-Boltzmann constant, h c is the heat transfer coefficient, k is thermal conductivity, is thermal diffusivity, and A is pixel area. The heat transfer coefficient is calculated for a forced convection scenario because windy conditions were present during the acquisition periods (Harris 2013;Thompson and Ramsey 2020a). The fraction of exposed melt on the surface of the flow is calculated based on previous work deriving sub-pixel temperatures (Dozier 1981;Rothery et al 1988;Harris 2013).…”
Section: High-resolution Ground-based Datamentioning
confidence: 99%
“…However, temperature was never considered a controlling variable. Prior emissivity measurements quantified the effects of surface roughness, state changes (melt vs. solid), and particle size (e.g., Simurda et al 2019;Williams and Ramsey 2019;Thompson and Ramsey 2020a). High temperature studies of cooling lava found that emissivity is significantly lower than previous assumed (Abtahi et al 2002;Lee et al 2013;Thompson and Ramsey 2020a,b).…”
Section: Introductionmentioning
confidence: 99%